STUDI PERBANDINGAN PENGELOLAAN PONDOK PESANTREN HIDAYATUL QOMARIYAH DENGAN PONDOK PESANTREN HIDAYATUL MUBTADIIN KOTA BENGKULU - Syaiful Bahri (Manajer Pendididikan, 2015)
The purpose of this research were to compare about eight standard management of education. There were; 1. Curriculum; 2. Teacher and school staff’s background; 3. Financial; 4.Infrastructure; 5. School organizing; 6. The function of Pondok Pesantren principle; 7. Student’s input and output; 8. Parents’ role. The research used comparative study. Data collection techniques were interview, observation and documentation study.The subject of the research are school principle, teachers, Pondok Pesantren’s staff, and students. The result show that the student management in Pondok Pesanteren Hidayatul Qomariah is more better than Pondok Pesantren Hidayatul Mubtadiin.Key words: differences, management